[1992] Proceedings. 11th IAPR International Conference on Pattern Recognition
DOI: 10.1109/icpr.1992.201521
|View full text |Cite
|
Sign up to set email alerts
|

Robust detection of facial features by generalized symmetry

Abstract: Locating facial features is crucial for various face recognition schemes. We suggest a robust facial feature detector based on a generalized symmetry interest operator. No special tuning is required af the face occupies 15-60% of the image. The operator was tested on a large face data base with a success rate of over 95%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 10 publications
0
45
0
2
Order By: Relevance
“…Specifically, we were interested in determining whether misorientations along certain axes were particularly disruptive for performance. Vertical bilateral symmetry is often considered an important defining attribute of faces [Reisfeld and Yeshurun, 1992;Thornhill and Gangested, 1993;Sun et al, 1998]. We expected, therefore, that detection performance would be disrupted disproportionately for orientations that destroyed the vertical bilateral symmetry.…”
Section: Resultsmentioning
confidence: 93%
“…Specifically, we were interested in determining whether misorientations along certain axes were particularly disruptive for performance. Vertical bilateral symmetry is often considered an important defining attribute of faces [Reisfeld and Yeshurun, 1992;Thornhill and Gangested, 1993;Sun et al, 1998]. We expected, therefore, that detection performance would be disrupted disproportionately for orientations that destroyed the vertical bilateral symmetry.…”
Section: Resultsmentioning
confidence: 93%
“…We have recently demonstrated the applicability of such an approach to face recognition. We have developed a system that automatically detects the most important facial features (eyes and mouth) using generalized symmetry 26,5]. We have also shown that normalizing a 2D image of a face using an a ne transformation determined by the location of the eyes and mouth is an e ective step towards face recognition 11].…”
Section: Introductionmentioning
confidence: 99%
“…Early work on face recognition was done by Sakai et al in [105] [104]. From their paper it is not apparent how they determine whether a feature is the eye or the nose, i.e.…”
Section: Feature Extractionmentioning
confidence: 99%